Sistem Pakar Penentuan Jenis Kulit Wajah Menggunakan Metode Dempster Shafer - Kotimah, Kusnul; Chandra, Albert Yakobus (CV. Information Technology Training Center - Indonesia (ITTC), 2022)
Omah Milla is a beauty treatment center that provides services from head to toe. One of the existing facilities is consulting services to determine the right treatment, but until now the consultation facility is only served offline. In order to continue to develop in improving services, Omah Milla wants to present an online consultation system that can be accessed by everyone so that customers can consult at anytime and anywhere. In addition, the general public can also use this system to check facial skin types, so they don't need to hesitate to determine the type of facial skin and use the right skincare. In this study, an expert system was created to determine the type of facial skin. The method used was the dempster shader. The flow of using this system is firstly the user is asked to choose the symptoms experienced, then the system processes it by calculating the dempster shafer and the results of the skin type can be directly seen by the user. This system has gone through the functionality test phase and everything is running and functioning well. To determine the accuracy of the system, the researcher compared 50 data from experts with an expert system and this study has an accuracy value of 100%.